A novel optimal formula of nickel extraction: arsenic removal from niccolite by controlling arsenic-containing phases - Tang, Xiaowei; He, Yuehui (Frontiers in Chemistry, 2023)
Objective: Niccolite, a rare nickel arsenide mineral, has emerged as a promising source for nickel extraction. However, its processing is limited and often associated with toxicity concerns. This study aims to search for efficient separation of arsenic during the roasting process of niccolite. Methods: The arsenic-containing phase was optimized through changing the contents of oxygen, additive S, and additive FeS in the system to achieve efficient separation of arsenic during the roasting process of niccolite. Thermodynamic analysis was performed using the equilibrium composition module with HSC Chemistry. Results: The thermodynamic results showed that in direct roasting, the product contained ferric arsenate which immobilized arsenic in the solid phase, increasing the difficulty in separation. In the presence of sulfur, the arsenic may escape completely in the form of gas (As2O3, As4O4, As4O6). The use of FeS as the reductant significantly reduced the residual arsenic content. Conclusion: The FeS reduction in roasting process is an optimal strategy for arsenic removal from niccolite. This provides a novel technique for nickel extraction in industry.